Familial Ectrodactyly and Its Ocular Associations - Muhammad Sultan, Ejaz Ahmad Javed (Pakistan Journal of Ophthalmology, 2008)
Purpose: To report a novel family of Ectrodactyly and its associations with eye pathology. Material And Methods: This observational and analytical study was conducted at Allied Hospital, Punjab Medical College (PMC), Faisalabad, from March 15 to April 15, 2007. A detailed history, examination and investigation of three families of Ectrodactyly were completed. Results: All members of three families had same findings in hands and feet. All were mentally sharp. They were all suffering from Myopia and cataract. Conclusion: The familial Ectrodactyly is associated with Myopia and cataract. No other eye findings were seen.